Urinary Measurement of Epigenetic DNA Modifications: A Non‐Invasive Assessment of the Whole‐Body Epigenetic Status in Healthy Subjects and Colorectal Cancer Patients. Issue 6 (15th November 2016) - Rozalski, Rafal; Gackowski, Daniel; Siomek‐Gorecka, Agnieszka; Banaszkiewicz, Zbigniew; Olinski, Ryszard
Abstract: Active mechanism of DNA demethylation can be responsible for the activation of previously silenced genes. Products of 5‐methylcytosine oxidation are released into the bloodstream and eventually excreted with urine. Therefore, whole‐body epigenetic status can be assessed non‐invasively on the basis of the urinary excretion of a broad spectrum of epigenetic modifications: 5‐hydroxymethylcytosine (5‐hmCyt), 5‐formylcytosine (5‐fCyt), 5‐carboxycytosine (5‐caCyt), and 5‐hydroxymethyluracil (5‐hmUra). We have developed a specific and sensitive, isotope‐dilution, automated, online, two‐dimensional ultra‐performance liquid chromatography system with tandem mass spectrometry (2D UPLC–MS/MS) to measure 5‐hmCyt, 5‐fCyt, 5‐caCyt, and their deoxynucleosides in the same urine sample. Human urine contains all of the modifications except from 5‐formyl‐2′‐deoxycytidine (5‐fdC) and 5‐carboxy‐2′‐deoxycytidine (5‐cadC). A highly significant difference in the urinary excretion of 5‐(hydroxymethyl)‐2'‐deoxycytidine (5‐hmdC) was found between healthy subjects and colorectal cancer patients (3.5 vs. 7.8 nmol mmol −1 creatinine, respectively), as well as strong correlations between the majority of analyzed compounds. Abstract : Health check : Two‐dimensional ultra‐performance liquid chromatography with tandem mass spectrometry (2D UPLC–MS/MS) is applied for the analysis of the TET‐mediated active DNA demethylation products, such as modified deoxynucleosides and bases, in urine. Human urine contains all the modifications except from 5‐formyl‐2′‐deoxycytidine (5‐fdC) and 5‐carboxy‐2′‐deoxycytidine (5‐cadC).